I Am Homeless. Now What? - Marcia Amidon Lusted
To be without a permanent home is markedly upsetting for any person$1 (Bs wellbeing and development. This compassionate book balances personal anecdotes from real young people in troubled situations with valuable resources to help out anyone in such an unfortunate situation. Whether it$1 (Bs a friend in need or a reader personally dealing with this kind of crisis, there are easily applicable, real-world suggestions on how to stay off the streets or use the resources that are available for those who are homeless. Testimony from real voices informs this fundamental guide to street life safety.s